Regional natural ark, guarantee label, flexibility, rural tourism, suburban area, hydrorecreationg resort. - Lardiés Bosque, Raúl (Geographicalia, 2017)
Important economic, social and cultural changes have emerged in the EU countries in the context of global economic restructuring. This restructuring has led to changes in tertiary sector of the European economy, the increase of international exchanges, and the socio-spatial mobility of the population.The aim of this paper is to examine new types of mobility between EU countries generated within the setting of internationalization and economic restructuring. First, the flow, direction, volume and evolution of international migration is reviewed. Second, migration development; academic mobility, skilled international migration, international retirement migration, and the increase of the movements due to tourist motivations to Mediterranean areas are analysed.